General practice in the Nordic countries - Kim Rose Olsen; Anders Anell; Unto Häkkinen; Tor Iversen; Thorhildur Ólafsdóttir; Matt Sutton (University of Oslo, 2016)
Background: General practice systems in the Nordic countries share certain common features. The sector is based on the Nordic model of a tax-financed supply of services with a political objective of equal access for all. The countries also share the challenges of increased political expectations to deliver primary prevention and increased workload as patients from hospital care are discharged earlier. However, within this common framework, primary care is organized differently. This is particularly in relation to the private-public mix, remuneration systems and the use of financial and non-financial incentives. Objective: The objective of this paper is to compare the differences and similarities in primary care among the Nordic countries, to create a mapping of the future plans and reforms linked to remuneration and incentives schemes, and to discuss the pros and cons for these plans with reference to the literature. An additional objective is to identify gaps in the literature and future research opportunities. Results/Conclusions: Despite the many similarities within the Nordic health care systems, the primary care sectors function under highly different arrangements. Most important are the differences in the gate-keeping function, private versus salaried practices, possibilities for corporate ownership, skill-mix and the organisational structure. Current reforms and political agendas appear to focus on the side effects of the individual countries' specific systems. For example, countries with salaried systems with geographical responsibility are introducing incentives for private practice and more choices for patients. Countries with systems largely based on private practice are introducing more monitoring and public regulation to control budgets. We also see that new governments tends to bring different views on the future organisation of primary care, which provide considerable political tension but few actual changes. Interestingly, Sweden appears to be the most innovative in relation to introducing new incentive schemes, perhaps because decisions are made at a more decentralised level. Published: April 2016.